Osteoblast Response to Copper-Doped Microporous Coatings on Titanium for Improved Bone Integration - Lai-jie Wang; Xiao-hui Ni; Fei Zhang; Zhi Peng; Fu-xun Yu; Lei-bing Zhang; Bo Li; Yang Jiao; Yan-kun Li; Bing Yang; Xing-yuan Zhu; Quan-ming Zhao (Nanoscale Research Letters, 2021)
Abstract Due to their excellent mechanical properties and good biocompatibility, titanium alloys have become a popular research topic in the field of medical metal implants. However, the surface of the titanium alloy does not exhibit biological activity, which may cause poor integration between the interface of the titanium implant and the interface of the bone tissue and subsequently may cause the implant to fall off. Therefore, surface biological inertness is one of the problems that titanium alloys must overcome to become an ideal orthopedic implant material. Surface modification can improve the biological properties of titanium, thereby enhancing its osseointegration effect. Copper is an essential trace element for the human body, can promote bone formation and plays an important role in maintaining the physiological structure and function of bone and bone growth and development. In this study, a microporous copper-titanium dioxide coating was prepared on the surface of titanium by microarc oxidation. Based on the evaluation of its surface characteristics, the adhesion, proliferation and differentiation of MC3T3-E1 cells were observed. A titanium rod was implanted into the rabbit femoral condyle, and the integration of the coating and bone tissue was evaluated. Our research results show that the microporous copper-titanium dioxide coating has a nearly three-dimensional porous structure, and copper is incorporated into the coating without changing the structure of the coating. In vitro experiments found that the coating can promote the adhesion, proliferation and differentiation of MC3T3-E1 cells. In vivo experiments further confirmed that the titanium copper-titanium dioxide microporous coating can promote the osseointegration of titanium implants. In conclusion, copper-titanium dioxide microporous coatings can be prepared by microarc oxidation, which can improve the biological activity and biocompatibility of titanium, promote new bone formation and demonstrate good osteoinductive properties. Therefore, the use of this coating in orthopedics has potential clinical application.